The Implication of ICT (Information and Communication Technology) based learning to increase students' learning motivation - Eliyanti, Marlina; Dodi, Mas (International Conference on Elementary Education, 2020)
This study aims to Determine: (1) differences in learning motivation of fifth grade students at Prajawinangun Wetan 2 Public Elementary School, Cirebon Regency before and after Obtaining ICT-based learning; (2) there is an increase of in the learning motivation of students in grade V at SD Negeri 2 Prajawinangun Wetan, Cirebon Regency. The design of this study was pre-experimental design (non-design) with one-group pretest-posttest design models. The Data analysis technique used is quantitative descriptive analysis. The research subjects were all students of grade V of SD Negeri 2 Prajawinangun Wetan, amounting to 27 students. Data collection using questionnaire guidelines, and observation guidelines with a 5 Likert scale model attitude. Based on the test results indicate a change in learning motivation of students before and after Obtaining ICT-based learning. This can be seen from the results of the N-Gain test analysis of 0.68 with the medium category on the questionnaire sheet, and 0.68 with the medium category on the observation sheet. The hypothesis that has been prepared has proven that the application of ICT-based learning can improve students' learning motivation